COMPARATIVE ANALYSIS OF SMART CATALYSTS FOR CO? REDUCTION: FROM MOLECULAR DESIGN TO LAB-SCALE PERFORMANCE - Nampira, Ardi Azhar; Mendes, Clara; Costa, Tiago (Yayasan Adra Karima Hubbi, 2025)
The electrochemical reduction of carbon dioxide (CO?) is a critical strategy for mitigating climate change and producing value-added chemicals, yet the development of highly selective catalysts remains a primary challenge. This study aimed to conduct a rigorous comparative analysis of three distinct classes of